INDONESIAN'S WOMEN MOVEMENT IN SUPPORTING INDONESIAN GOVERMENT POLICY (GOVERMENT REGULATION NO. 2 - 2017) - Nieke Monika Kulsum (Universitas Nasional, 2019)
AbstractIndonesia has become independent country since 1945, however this country still facing many internal conflicts. The power of Soeharto (the second Indonesian President) regime that lasted for 32 years, spread fears to many people which make them silenced. After the reformation in 1998 that led to the collapsed of that regime, Indonesia experienced a period of “freedom from fear”. Since then there are many new mass organizations emerged in Indonesia. Some of these mass organizations are arrogance and causes fear to Indonesian people. Therefore, in the current era of president Jokowi leadership, the government acts firmly on those mass organizations by issuing Government Regulation No.2 which was signed on July 10, 2017. Moreover, this new regulation has raised pros and contras in society. One group of people who care about this is the Women Indonesian Care Group which consists of women from various segments on a racial, religious, educational, work and age basis. The researcher is interested to raise this matter as a research because it is a new thing in Indonesia where group consisting mostly of mothers perform an action in the form of a demonstration conducted in front of Parliament Building/House of Representative on Friday, July 27, 2017. It turns out that those mothers who have been upset and disturbed by the actions done by certain mass organizations. Thus they feel the need to do the demonstration. The method of this research is qualitative, researchers will conduct interviews with the perpetrators of demos, documentation studies and literature studies. Research is still underway until now.